Moldability and solvent debinding of hydroxyapatite micro-part processed through micro-powder injection molding - Al Basir,; Norhamidi Muhamad,; Abu Bakar Sulong,; Mohammad Fadhli Izuddin Mohd Nor,; Muhammad bin Mohamed Amin,; Nashrah Hani Jamadon, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The development of the micro-powder injection molding (μPIM) process from the powder injection molding (PIM) process has been prompted by the demand of the worldwide market to produce micro-sized components. The need for μPIM-processed components is currently rising across a range of industries, including automotive, aerospace, food, biomedical, electronics, and telecommunications. In the current research work, homogeneous HA feedstock with a powder loading of 57 vol.% was prepared by mixing HA powder particles with palm stearin and low-density polyethylene (LDPE) binders at a mixing temperature of 150 °C for 6 h. Defect-free injection molded or green micro-sized components of HA were produced by employing injection pressure, injection time, mold temperature, and melt temperature of 12 bar, 5 s, 110 °C, and 180 °C, respectively. When mold temperatures less than 110 °C were used, short shot defects were frequently observed in green specimens. After solvent debinding at 60 °C for 50 min, 82.2% of the palm stearin was removed from the green part. No difference in dimension between the solvent debound part and the green part was noticed. An open-pore structure developed in the solvent debound HA micro-component is helpful for eliminating the insoluble LDPE binder during the thermal debinding phase.